ANTIBIOTIC SUSCEPTIBILITY PATTERN OF METHICILLIN RESISTANCE STAPHYLOCOCCUS AUREUS (MRSA) AMONG PEDIATRIC AND YOUNG ADULT PATIENT (The Research of Medical Science Review, 2025)
Staphylococcus aureus, a gram-positive bacterium, poses significant health risks due to its methicillin-resistant strain (MRSA), which is resistant to many antibiotics. MRSA can cause various infections, including skin infections, pneumonia, and sepsis, with differing impacts on children and adults. Over 90% of S. aureus strains carry plasmids encoding beta-lactamase, and some are resistant to beta-lactam antibiotics like methicillin due to alterations in penicillin-binding proteins (PBPs). MRSA is widespread in hospitals, and treatment strategies depend on local resistance patterns. The objectives of this study were to determine the prevalence of MRSA infections in pediatric and young adult patients and to analyze the antibiotic susceptibility patterns of MRSA isolates. This cross-sectional study utilized convenience sampling with 107 participants divided into two groups: pediatric (0-12 years) and young adults (12-30 years), conducted at City Medical Hospital. Microbiological techniques, including bacterial culture, Gram staining, and biochemical tests, were employed. Antibiotic susceptibility was assessed using the Kirby-Bauer method, and data were analyzed using SPSS software version 25 with descriptive statistics.The prevalence of MRSA was 75% in adults and 91% in pediatric patients, with higher rates observed in children around one month old. Females showed a higher prevalence in both groups. In pediatrics, MRSA was predominantly found in blood specimens, while pus specimens were more common in adults. Cefoxitin demonstrated 100% sensitivity in adults, followed by ciprofloxacin (92.3%). High resistance was noted for erythromycin, chloramphenicol, linezolid, and penicillin. Pediatric isolates showed 100% sensitivity to cefoxitin, tigecycline, chloramphenicol, and linezolid, with gentamicin, co-trimoxazole, and doxycycline showing 80% sensitivity. Resistance rates were highest for penicillin (97.6%), ciprofloxacin (84.6%), and erythromycin (79.6%) in pediatrics. Linezolid and chloramphenicol were effective in both age groups, while doxycycline showed better results in adults. This study highlights significant differences in the prevalence and antibiotic susceptibility patterns of MRSA between pediatric and young adult patients, with higher prevalence in infants and a greater impact on females. Pus was the primary source of MRSA in adults, while blood was predominant in pediatrics. Doxycycline, linezolid, and chloramphenicol emerged as effective treatment options, while erythromycin and penicillin showed high resistance in both groups.